INDICATORS MODALITY OF CEREBRAL HEMODYNAMICS TEENAGERS WITH BEER CONSUMPTION - Galina Albertovna Novikova; Andrey Gorgonevich Soloviev; Lubov Ivanovna Gubareva; Lyubov Albertovna Novikova (Наука. Инновации. Технологии)
The article describes the results of a survey of 134 adolescent boys, carried out with the aim of studying modality indicators of the state of cerebral hemodynamics teenagers with beer alcoholism. We found a significant circulatory disorders in the brain in adolescents depending on the day of drinking beer. As indicators of estimating cerebral hemodynamics in teenagers with beer alcoholism noted: the increase in pulse blood and vasodilatation; the presence of spasm of peripheral vessels; change the state of tone and elasticity of blood vessels; violation of vascular tone of the initial part of the microvasculature, arterioles and precapillary's; violation of the venous outflow. These indicators can be used to assess the toxic effect of beer on the physiology of adolescents and install the latest days of consumption.